A New Approach of Electronics and Photonics Convergence on Si CMOS Platform: How to Reduce Device Diversity of Photonics for Integration. (11th June 2008) - Wada, Kazumi
Abstract : Integrated photonics via Si CMOS technology has been a strategic area since electronics and photonics convergence should be the next platform for information technology. The platform is recently referred to as "Si photonics" that attracts much interest of researchers in industries as well as academia in the world. The main goal of Si Photonics is currently to reduce material diversity of photonic devices to pursuing CMOS-compatibility. In contrast, the present paper proposes another route of Si Photonics, reducing diversity of photonic devices. The proposed device unifying functionality of photonics is a microresonator with a pin diode structure that enables the Purcell effect and Franz-Keldysh effect to emit and to modulate light from SiGe alloys.